AMPK in Intestinal Health and Disease: A Multifaceted Therapeutic Target for Metabolic and Inflammatory Disorders - Yibcharoenporn C; Muanprasat C; Moonwiriyakit A; Satitsri S; Pathomthongtaweechai N (Drug Design, Development and Therapy)
Chamnan Yibcharoenporn,* Chatchai Muanprasat,* Aekkacha Moonwiriyakit, Saravut Satitsri, Nutthapoom Pathomthongtaweechai Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samut Prakan, 10540, Thailand*These authors contributed equally to this workCorrespondence: Nutthapoom Pathomthongtaweechai, Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bang Phli, 111 Moo 14, Bang Pla, Bang Phli, Samut Prakan, 10540, Thailand, Tel +66984800365, Email nutthapoom.pat@mahidol.eduAbstract: The intestines play essential roles in nutrient absorption and immune function and help maintain a protective barrier. Disruptions to its function can result in various diseases, including metabolic disorders, inflammation, and cancer. As a key regulator of cellular energy levels, 5’-adenosine monophosphate-activated protein kinase (AMPK) is essential for intestinal health. Beyond its established metabolic role, emerging evidence suggests that AMPK exerts profound effects on intestinal cell physiology, influencing cell proliferation and differentiation, inflammation, autophagy, barrier integrity, and smooth muscle contractility. Here, we explore the structure and regulation of AMPK, as well as its diverse roles in intestinal diseases and potential as a therapeutic target. Our findings reveal that AMPK is a multifaceted regulator of intestinal health, modulating various cellular processes and intestinal diseases. It plays a dual role in cancer, acting as both a tumor suppressor and promoter, and it regulates inflammatory pathways, autophagy, tight junction formation, and smooth muscle contractility. Both natural and synthetic AMPK activators offer promise as therapeutic agents. This review of AMPK’s mechanisms and activators offers valuable insights for developing novel therapies for intestinal disorders. Further research is needed to fully define AMPK’s roles and therapeutic potential.Keywords: AMPK, AMPK activators, intestinal diseases, intestinal inflammation, intestinal cancer